Synthesis and Characterisation of Cr(III), Fe(II) and Pd(II) Complexes with 4-Methyl Isonitrosoacetophenone - Raut, R.D.; Patil, M.R. (Asian Journal of Chemistry, 2010)
Studies of the complexes of transition metal ions with ligand 4-methyl isonitrosoacetophenone have been carried out on the basis of elemental analysis, molar conductance, electronic spectra etc. The complexes have been assigned the formula Cr(IMAP)3, Fe(IMAP)2, Pd(IMAP)2. Attempts have been made to assign possible structures with the help of magnetic data, electronic and IR spectra.